Practice Variability Combined with Task-Oriented Electromyographic Biofeedback Enhances Strength and Balance in People with Chronic Stroke - Peih-Ling Tsaih; Ming-Jang Chiu; Jer-Junn Luh; Yea-Ru Yang; Jiu-Jenq Lin; Ming-Hsia Hu (Behavioural Neurology)
Objectives. To investigate the effects of practice variability combined with task-oriented electromyographic biofeedback (EMGBFB) on strength and balance in people with chronic stroke. Methods. Thirty-three participants were randomly assigned into the constant force EMGBFB tibialis anterior (TA) exercise (constant) group, the variable force EMGBFB tibialis anterior exercise (variable) group, or the upper extremity exercise without EMGBFB (control) group. Subjects in each group received 6 weekly sessions of exercise training (18 sessions, 40 minutes each). Motor outcomes were TA strength, balance (anteroposterior sway amplitude defined by limits of stability test in dynamic posturography), walking speed, Timed Up and Go test (TUGT), and six-minute walk test (6MWT). Data were measured at baseline, 1 day, 2 weeks, and 6 weeks posttraining. Results. TA strength increased significantly in both the constant and variable groups after training. Balance significantly improved only in the variable group. All participants showed improvements in walking speed, TUGT, and 6MWT. Conclusions. Task-oriented EMGBFB-assisted TA exercise training improved muscle strength in people with chronic stroke. Practicing to reach varying force levels during EMGBFB-assisted tibialis anterior exercises facilitated improvements in the ability to sway in the anteroposterior direction while standing. Our findings highlight the importance of task-oriented and motor learning principles while using the EMGBFB as an adjunct therapy in stroke rehabilitation. This trial was registered with trial registration number NCT01962662.